Analysis of the influence of heat loss factors on the overall performance of utility-scale parabolic trough solar collectors. (1st November 2018) - Xu, Li; Sun, Feihu; Ma, Linrui; Li, Xiaolei; Yuan, Guofeng; Lei, Dongqiang; Zhu, Huibin; Zhang, Qiangqiang; Xu, Ershu; Wang, Zhifeng
Abstract: For parabolic trough solar collectors, several factors (such as the amount of the gas in the evacuated annulus, the absorber emissivity, the wind speed and temperature distributions of the absorber, the glass envelope and the heat transfer fluid) are critical to influence their heat losses and consequently their overall performance. Therefore, this study develops a mathematical model for thermal behaviors of parabolic trough solar collectors in consideration of these impact factors. Additionally, to validate this model, experimental data were measured for a test facility. This facility includes a utility-scale loop of parabolic trough solar collectors which can be applicable to solar thermal power plants. The comparison indicates a good agreement between predicted and measured temperatures of the heat transfer fluid at the outlet of the collectors. Using this model, parametric studies were conducted for impact factors. These factors are the pressure of the H2 or air from 0.01 to 1E5 Pa, the absorber emissivity from a measured basis to its four times, the wind speed from 2 to 12 m/s, and temperature distributions with and without the concentrated solar flux. Consequently, several conclusions were drawn by analyzing how they influence heat losses and further overall performance under specified boundary conditions. Graphical abstract: Image Highlights: Model was validated with experiment data for utility-scale PTCs. Parametric studies were made to analyze critical heat loss factors. Effects of these factors on overall performance are quantified respectively. H2 's effective thermal conductivity is much larger than air's in tube annulus. Wind speed barely affects heat losses due to perfect vacuum tubes.